The CannTeen Study: Cannabis use disorder, depression, anxiety, and psychotic-like symptoms in adolescent and adult cannabis users and age-matched controls. (December 2022) - Lawn, Will; Mokrysz, Claire; Lees, Rachel; Trinci, Katie; Petrilli, Kat; Skumlien, Martine; Borissova, Anna; Ofori, Shelan; Bird, Catherine; Jones, Grace; Bloomfield, Michael AP; Das, Ravi K; et al.
Background: Adolescence is characterised by psychological and neural development. Cannabis harms may be accentuated during adolescence. We hypothesised that adolescents would be more vulnerable to the associations between cannabis use and mental health and addiction problems than adults. Method: As part of the 'CannTeen' study, we conducted a cross-sectional analysis. There were 274 participants: split into groups of adolescent users ( n  = 76; 16–17 years old) and controls ( n  = 63), and adult users ( n  = 71; 26–29 years old) and controls ( n  = 64). Among users, cannabis use frequency ranged from 1 to 7 days/week, while controls had 0–10 lifetime exposures to cannabis. Adolescent and adult cannabis users were matched on cannabis use frequency (mean=4 days/week). We measured Diagnostic and Statistical Manual (DSM-5) Cannabis Use Disorder (CUD), Beck Depression Inventory, Beck Anxiety Inventory and Psychotomimetic States Inventory-adapted. Results: After adjustment for covariates, adolescent users were more likely to have severe CUD than adult users (odd ratio = 3.474, 95% confidence interval (CI) = 1.501–8.036). Users reported greater psychotic-like symptoms than controls ( b  = 6.004, 95% CI = 1.211–10.796) and adolescents reported greater psychotic-like symptoms than adults ( b  = 5.509, 95% CI = 1.070–9.947). User-group was not associated with depression or anxiety. No significant interactions between age-group and user-group were identified. Exploratory analyses suggested that cannabis users with severe CUD had greater depression and anxiety levels than cannabis users without severe CUD. Conclusion: Adolescent cannabis users are more likely than adult cannabis users to have severe CUD. Adolescent cannabis users have greater psychotic-like symptoms than adult cannabis users and adolescent controls, through an additive effect. There was no evidence of an amplified vulnerability to cannabis-related increases in subclinical depression, anxiety or psychotic-like symptoms in adolescence. However, poorer mental health was associated with the presence of severe CUD.